2009
DOI: 10.1111/j.1464-410x.2009.08682.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgical management of pelvic‐ureteric junction obstruction: update on the current status of robotic‐assisted pyeloplasty

Abstract: BACKGROUND Pelvi‐ureteric junction (PUJ) obstruction is characterized by a functionally significant impairment of urinary transport caused by intrinsic or extrinsic obstruction in the area where the ureter joins the renal pelvis. The majority of cases are congenital in origin; however, acquired conditions at the level of the ureteropelvic junction may also present with symptoms and signs of obstruction. Historically, open pyeloplasty and endoscopic techniques have been the main surgical options with the intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 38 publications
2
32
0
1
Order By: Relevance
“…Clinical trials have shown that robotic pyeloplasty is a safe, feasible and effective procedure for treating UPJO. 35 A review and meta-analysis of the literature demonstrated that robotic pyeloplasty was associated with a 10-min reduction in operative time and significantly shorter hospital stays compared with the LP approach. However, there were no differences between the techniques concerning the rates of success and complications.…”
Section: Robot-assisted Pyeloplastymentioning
confidence: 99%
“…Clinical trials have shown that robotic pyeloplasty is a safe, feasible and effective procedure for treating UPJO. 35 A review and meta-analysis of the literature demonstrated that robotic pyeloplasty was associated with a 10-min reduction in operative time and significantly shorter hospital stays compared with the LP approach. However, there were no differences between the techniques concerning the rates of success and complications.…”
Section: Robot-assisted Pyeloplastymentioning
confidence: 99%
“…8,9 Recent reports suggest that robotassisted pyeloplasty has equivalent success rates. 3,5 Minimally invasive surgery also offers the additional advantage of decreased postoperative pain and shorter convalescence in many of the adult series. 3,5,6 As an alternative to minimally invasive pyeloplasty, endopyelotomy has a lower success rate of 60% to 80%.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…3,5 Minimally invasive surgery also offers the additional advantage of decreased postoperative pain and shorter convalescence in many of the adult series. 3,5,6 As an alternative to minimally invasive pyeloplasty, endopyelotomy has a lower success rate of 60% to 80%. 7,10 It has thus fallen out of favor as first-line therapy for primary UPJ obstruction, but it is still often used in secondary UPJ obstruction or for patients who are poor operative candidates.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure lasts 1.5 hours in experienced hands and has a success rate of >95 per cent. 4 Anastomotic leaks are rare and many patients can go home on the day after RAP. Kidneys with anatomical abnormalities can be treated 5 and functional or symptomatic recurrence seems rare at three years follow-up.…”
Section: Robotic-assisted Pyeloplasty (Rap)mentioning
confidence: 99%